2022
DOI: 10.1111/acps.13405
|View full text |Cite
|
Sign up to set email alerts
|

Mental health in people with minority sexual orientations: A meta‐analysis of population‐based studies

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(84 citation statements)
references
References 71 publications
7
73
1
3
Order By: Relevance
“…The former finding is consistent with a US study reporting a higher prevalence of ACEs and a higher mean ACE score among bisexuals compared to both heterosexuals and homosexuals 11 . The observed greater burden of mental health problems in Danish bisexuals also accords well with other findings from the US, Australia and a recent metaanalysis, where bisexuality was more strongly associated with a range of mental health problems than heterosexual and homosexual orientations 13,15,26 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The former finding is consistent with a US study reporting a higher prevalence of ACEs and a higher mean ACE score among bisexuals compared to both heterosexuals and homosexuals 11 . The observed greater burden of mental health problems in Danish bisexuals also accords well with other findings from the US, Australia and a recent metaanalysis, where bisexuality was more strongly associated with a range of mental health problems than heterosexual and homosexual orientations 13,15,26 .…”
Section: Discussionsupporting
confidence: 90%
“…A markedly higher prevalence of mental health problems among non-heterosexual than heterosexual individuals has also been previously reported in other datasets [12][13][14]25,26 . This increased mental morbidity may be interpreted within the frame of "minority stress", where adverse phenomena such as stigma, prejudice, discrimination and exclusion produce a hostile and distressing social environment for non-heterosexuals, leading to higher rates of mental health problems 13,26 . In a Danish context, we observed that stigma-related experiences are remarkably common in nonheterosexual persons.…”
Section: Discussionsupporting
confidence: 81%
“…LGBT persons have previously been described to be more vulnerable for mental health problems compared to non‐LGBT population, experiencing higher levels of psychological distress, social anxiety, depression, and loneliness (Almeida et al, 2009 ; Anderssen et al, 2020 ; Eres et al, 2021 ; Hsieh & Liu, 2021 ; Hughes, 2018 ; Valentine & Shipherd, 2018 ; Wittgens et al, 2022 ). Also during the pandemic, lower levels of well‐being in LGBT compared with cis‐heterosexuals have been reported, as well as a higher risk for depressive symptoms in asexual, bisexual, non‐binary, and trans individuals (Buspavanich et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, because of cross-national differences in the prevalence of mental disorders generally, it is unclear if cross-national differences in mental health outcomes among LGB individuals are actually specific to LGB individuals or simply reflect more general differences in the prevalence of mental disorders across countries. Some cross-national evidence for disparities in mental health outcomes (specifically depression, anxiety disorders, and alcohol use disorders) between LGB and heterosexual individuals also comes from meta-analyses [ 20 , 21 ]. However, studies assessing mental health disparities between LGB and heterosexual individuals across a broad range of mental disorders in a cross-national sample, including Western and non-Western countries, are lacking [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some cross-national evidence for disparities in mental health outcomes (specifically depression, anxiety disorders, and alcohol use disorders) between LGB and heterosexual individuals also comes from meta-analyses [ 20 , 21 ]. However, studies assessing mental health disparities between LGB and heterosexual individuals across a broad range of mental disorders in a cross-national sample, including Western and non-Western countries, are lacking [ 21 ].…”
Section: Introductionmentioning
confidence: 99%